Development of a caring teacher-student realationship in higher education - Simel Pranjić, Sanja (Journal of Education Culture and Society, 2021)
Aim. This article aims to summarize the current state of understanding on a development of a caring teacher-student relationship in higher education context, grounded in relational pedagogy. Also, it provides critical reflection on the data from available literature.Methods. The development of a caring teacher-student relationship was presented using the method of description, based on the review of relevant literature.Results. The development of a caring relationship between students and higher education teachers can be monitored in stages. At first, there is the introductory meeting with the students when a teacher with his personality, authenticity, and approach lays the foundations for the development of a caring relationship. During further meetings, the teacher encourages mutual trust, respect, and appreciation and deepens the relationship by adapting the teaching process to the needs, interests, and affinities of students, until the formal completion of their cooperation.Conclusion. In order to achieve a caring relationship with students in higher education, a teacher needs to approach it consciously, intentionally, thoughtfully and to plan it well from the very beginning. It is crucial to get to know the students as real persons, and accordingly, continuously adapt the teaching process to their needs and interests, allowing them to express themselves freely in a safe, accepting, and encouraging environment.Cognitive value. By presenting the stages of a development of the caring relationship between students and higher education teachers and the synthesis of their characteristics, this paper contributes to a deeper understanding of this phenomenon.